The Characteristics of Bioplastic Made from Sodium Alginate and Kappa Carrageenan - Putri, Dhiya Aflah Luswanto; Ridlo, Ali; Hartati, Retno (Universitas Diponegoro, 2025)
Synthetic plastic is commonly used daily, but its non-biodegradable nature poses a significant environmental threat. Therefore, it is urgent to explore sustainable alternatives such as bioplastics. Alginate, a polysaccharide, is a promising raw material for bioplastics. However, its poor elasticity characteristic necessitates the addition of other polysaccharides, such as carrageenan, to improve bioplastics' mechanical properties. This research aims to determine the characteristics (physical and mechanical properties) of bioplastics made from a mixture of alginate and kappa-carrageenan. The laboratory experimental methods were applied with a completely randomized design. The treatments are mixtures of alginate and k-carrageenan in the following ratios: 10:0 (A10K0), 8:2 (A8K2), 6:4 (A6K4), 4:6 (A4K6), 2:8 (A2K8), 0:10 (A0K10). The characteristics of bioplastic films measured were thickness, water resistance, tensile strength, elongation, and appearance. The optimal bioplastic formulation (4:6 ratio of k-carrageenan to alginate) exhibited a film thickness of 138.3 µm, 16.6% biodegradability, tensile strength of 22.965 N/mm², and 2.73% elongation. The scanning electron microscope showed that the surface structure of bioplastic A4K6 made fromthe ratios of k-carrageenan and alginate of 4:6 had fewer structure cracks and more surface smoothness.